RTHP-23. PROSPECTIVE TRIAL OF CONVENTIONALLY FRACTIONATED DOSE CONSTRAINTS FOR RE-IRRADIATION OF PRIMARY BRAIN TUMORS. (11th November 2019) - McGovern, Susan; Luo, Dershan; Johnson, Michael; Nguyen, Kham; Li, Jing; McAleer, Mary; Yeboa, Debra; Grosshans, David; Ghia, Amol; Chung, Caroline; Thall, Peter; Sulman, Erik; et al.
Abstract: PURPOSE/OBJECTIVE: Dose constraints for re-irradiation of recurrent primary brain tumors are not well-established, especially for treatment volumes too large for stereotactic radiotherapy. This prospective trial was performed to test dose constraints for conventionally-fractionated re-irradiation of recurrent primary brain tumors MATERIALS/METHODS: A single-institution, prospective trial of 21 adults with recurrent brain tumors was performed. Electronic dosimetry records from the first course of radiation (RT1) were obtained and deformed onto the simulation CT for the second course of radiation (RT2). Treatment plans for RT2 were developed that met protocol-assigned dose constraints for RT2 alone and the composite dose of RT1+RT2. Dose constraints were also based on histology and interval since RT1. The primary endpoint was the rate of symptomatic brain necrosis after RT2. RESULTS: Twenty one adults enrolled from March 2017 to May 2018. Twelve had glioblastoma, four had oligodendroglioma, two had anaplastic astrocytoma, and one each had choroid plexus papilloma, hemangiopericytoma, and pleomorphic xanthroastrocytoma (PXA). Twenty patients were treated with VMAT and one was treated with proton CSI. Median RT1-RT2 interval was 45 months (range, 9–141 months). Median RT2 dose was 42.8 Gy (range, 17.5–60 Gy). Median PTV volume was 208 cc (range, 7–1537 cc). Median imaging followup was 9 months (range, 1–20 months). Two months after RT2, the patient with PXA developed a trapped temporal horn adjacent to the RT2 treatment volume; pathology from emergent resection revealed necrotic brain tissue. The patient recovered fully and lived another 18 months until dying of disease progression. No other patient developed symptomatic radionecrosis. Median overall survival from RT2 for all patients was 11 months (range, 3–20 months). CONCLUSION: Re-irradiation can be performed with conventionally fractionated schemes. Given the low rate of symptomatic radionecrosis, the dose constraints described here are a starting point for future studies of conventionally fractionated re-irradiation.